Non-chemical Weed Management Principles, Concepts and Technology - Upadhyaya, Mahesh K (CABI, 2014)
The increased availability and acceptability of highly effective and selective synthetic herbicides in the decades following World War II diverted the focus of weed researchers and managers away from non-chemical weed management. Herbicides became the predominant option for weed control, with the ecological and social consequences of herbicide use being ignored or downplayed. An over-reliance on herbicide use led to the widespread development of herbicideresistant weeds and concerns about potential negative effects on human health and the environment. The sustainability of our food production systems and the health and environmental consequences of pesticide use are rapidly becoming important global issues. Organic farming is increasing in popularity in many parts of the world due to an increasing demand for pesticide-free food. Weeds pose a serious problem in organic farming. Several weed management options that were once labelled ‘uneconomic’ or ‘impractical’, and their technology development practically discontinued, are now being revisited.